2012
DOI: 10.1248/cpb.c12-00171
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Assessment of Patterns, Severity and Clinical Outcome of Indian Poisoning Incidents

Abstract: The objective of this study was to assess the patterns, severity and clinical outcome of poisoning incidents. A prospective assessment was conducted over a period of 1 year in tertiary-care teaching hospitals. Glasgow coma scale (GCS), poisoning severity score (PSS), and snake bite severity score (SSS) were used to predict the severity of poisoning, and then compared to the clinical outcome. The study involved 212 patients with a mean age of 26.7 12.7 years. Pesticides were found to be the most common poisonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 39 publications
(53 reference statements)
0
27
0
Order By: Relevance
“…The new poison information center organizes educational programs in and around the Mysore district to create awareness about poisoning substances and appropriate preventive measures. The results of current and previous[78917] studies indicate that new poison information center is providing critical services as envisaged for the center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The new poison information center organizes educational programs in and around the Mysore district to create awareness about poisoning substances and appropriate preventive measures. The results of current and previous[78917] studies indicate that new poison information center is providing critical services as envisaged for the center.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Unfortunately, majority of them are widely distributed across India and easily available for purchase due to lack of stringent regulatory laws, thereby influencing the incidence of poisoning. [13789] Recognizing the problem of poisoning and the need for awareness and specialized facilities to deal with it, poison information centers have been established in some parts of India. [123]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inter‐rater reliability of the PSS was established in the seminal, multicenter study of 14 poisoning centers that independently rated the PSS in 371 cases (Persson et al, ). Therefore, although gathering additional inter‐rater reliability data in the current sample would have strengthened the study, our focus was on testing the validity (not reliability) of the measure, an approach that has been typical of subsequent PSS validation research (Akdur et al, ; Churi et al, ; Peter et al, ; Sam et al, ). Finally, we did not compare the performance of the PSS with alternative, validated measures of acute medical morbidity such as the Glasgow Coma Scale (Teasdale & Jennett, ) that have been included in some prior PSS validation studies (Akdur et al, ; Churi et al, ; Sam et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Following its introduction and initial testing, evidence for the validity of the PSS has been based on studies of calls to Poison Centers (Bentur, Raikhlin-Eisenkraft, & Lavee, 2004;Casey, Dexter, Michell, & Vale, 1998;Wong, Taylor, Ashby, & Robinson, 2010) and poisoning patients presenting to hospital (Peter et al, 2013;Sabzghabaee et al, 2011;Thanacoody et al, 2016). This research has shown that the PSS predicts clinical outcomes including mortality (Peter et al, 2013;Sabzghabaee et al, 2011;Thanacoody et al, 2016) and that it is correlated with other validated measures of acute medical morbidity (Akdur et al, 2010;Churi, Ramesh, Bhakta, & Chris, 2012;Peter et al, 2013;Sam et al, 2009). A major limitation of this evidence is that it is based primarily on studies of single drug exposures including organophosphate (Akdur et al, 2010;Peter et al, 2013;Sam et al, 2009), carbon monoxide (Cevik et al, 2006), and methanol or ethylene glycol (Thanacoody et al, 2016).…”
mentioning
confidence: 99%